Pelaksanaan Pengabdian Masyarakat dalam Upaya Monitoring Penyakit Tuberculosis (TBC) di Puskesmas Baktiya Barat - Mansura Feby Amanda; Khesya Nayla Puspita Sari Ponda (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Tuberculosis (TB) remains a public health problem in Indonesia, ranking third in the world after India and China, with around 10% of the total global cases. TB is a lung infection caused by Mycobacterium tuberculosis, which is transmitted through the air when a sufferer coughs (Hidayah, 2018). In this community service activity, interviews were conducted with patients suspected of having TB based on clinical symptoms. The investigation was continued based on data from the Baktiya Barat Health Center, with the collection of sputum samples for TCM testing at the Tanah Jambo Aye Health Center. In addition to interviews and sampling, secondary TB data from 2023–2024 from the Baktiya Barat Health Center were also analyzed. The results showed that there were 25 TB patients: 13 males and 12 females, including two children (a 9-year-old boy and a 5-year-old girl) who underwent routine treatment at the health center and integrated health post. Sputum examination was carried out with standard collection and packaging procedures before being sent for TCM testing. The data showed that the number of male patients was slightly higher than female patients. In addition, there was an increase in cases of patients dropping out of treatment, with one case in 2024, compared to zero cases the previous year. In conclusion, TB remains a serious concern in Baktiya Barat District, with a total of 25 active cases requiring ongoing monitoring and treatment.